Performance Evaluation of the M2M Communication in the 4G Network (LTE/LTE-A) With Real Background Traffics: تقييم أداء نظم الاتصال M2M ضمن شبكات الجيل الرابع LTE/LTE-A المتضمنة حمل الشبكة الفعلي - Hala Adnan Fadel, Yasser Emleh, Ali Diab (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2020)
The applications of the fifth generation in 5G communications depend on the Internet Of Things (IOT), meaning that every person and everything will be connected to the Internet, so any tool or device in the house or in the street or any work place will be connected to the internet, and this leads us to the term Smart cities, i.e. data is formed everywhere by any person or any machine and is analyzed in a short time to obtain useful information in a timely manner such as monitoring the health status of patients and the elderly, and monitoring devices and tools at home and determining whether there is a malfunction or a lack of a substance, As well as analyzing the traffic situation in the streets and assisting and warning drivers Non-visual risks, which pave the way towards self-driving cars. Here, machine-to-machine (M2M) mobile communications play a pivotal role in enabling the effective and safe transfer of this information from machine to machine without human intervention at full speed and with minimal delay. This poses more challenges for the future network that must accommodate mobile data and the huge number of devices and sensors deployed everywhere in order to be a large-scale network with high capacity and efficiency [16, RODRIGUEZ.J]. In this article, several scenarios have been tested to evaluate the performance of M2M technology within 4Generation LTE / LTE-A networks by adding an external simulated network load. The results showed that the amount of data sent by the MMS sensors is fully received by the remote host, so we get 100% productivity. As for other applications, the productivity is around 99% and the average delay is relatively small as long as the network operates within the available transfer rates. In addition, the process of exchanging packages takes place almost completely (a small amount of losses).